Вивчення фармакокінетики морфоліній 2-(5-(4-піридил)-4-(2-метоксифеніл)-1,2,4-триазол-3-ілтіо)ацетату - Каплаушенко, Андрій Григорович; Каплаушенко, А. Г.; Kaplaushenko, A. G. (My University, 2013)
Впровадження в медичну практику нових високоефективних лікарських засобів є важливою складовою сучасної науки. Дослідження в ряді водорозчинних сполук – похідних 1,2,4-триазолу є перспективним напрямом рішення даної проблеми. На сьогодні відомо, що морфоліній 2-(5-(піридин-4-іл)-4-(2-метоксифеніл)-1,2,4-триазол-3-ілтіо)ацетат (Тіометрізол) є досить активною в біологічному аспекті речовиною [3, 4]. Розроблено також метод кількісного визначення даної сполуки в субстанції [5]. Подальше впровадження морфоліній 2-(5-(піридин-4-іл)-4-(2-метоксифеніл)-1,2,4-триазол-3-ілтіо)ацетату (Тіометрізолу) в медичну або ветеринарну практику потребує додаткових поглиблених досліджень фармакодинаміки цієї сполуки, що і стало метою роботи. Современная медицина и фармация используют достаточное количество лекарственных средств, которые относятся к разным классам соединений. Однако создание новых высокоэффективных и малотоксичных лекарственных средств с широким спектром биологической активности было и остается важным заданием фармацевтической науки. Особый интерес представляют гетероциклические соединения, а именно производные 1,2,4-тиазола, как потенциальные биологически активные вещества. Главной целью нашей работы является поиск среди производных 1,2,4-триазола биологически активных веществ. Объектом нашего исследования был 2-(5-(пиридин-4-ил)-4-(2-метоксифенил)-1,2,4-триазол-3- илтио)ацетат (Тиометризол). Известно, что данное соединение является достаточно активным в биологическом аспекте веществом. В ходе работы изучена фармакодинамика Тиомеризола на кролях. Проанализированы спектры поглощения образцов сыворотки крови, полученные после введения раствора морфолиний 2-(5-(пиридин-4-ил)-4-(2-метоксифенил)-1,2,4-триазол-3-илтио)ацетата и зарегистрирована характерная полоса поглощения данного вещества при 275 нм через 15 минут после введения. На основании спектрофотометрического изучения образцов крови и мочи животных, которым вводили Тиометризол, установлено, что данный потенциальный лекарственный препарат при его внутривенном введении сразу создает максимальную концентрацию в крови и через 32 часа не определяется ни в крови, ни в моче животных, таким образом является нетоксичным и может быть рекомендован для дальнейших испытаний. Present-day medicine and pharmacy use a lot of drugs that belong to different classes of compounds. However, the creation of new high-efficient and low-toxic drugs with wide spectrum of biological activity has been and still is an important task of the pharmaceutical science. Heterocyclic compounds, namely, 1,2,4-thiazole derivatives cause great interest to this regard as potential biologically active substances. The main purpose of the work is the synthesis of low-toxic and highly-efficient compounds as well as the search of biologically active substances among them. The object of our study was morpholinum 2-(5-(pyridin-4-yl)-4-(2-methoxyphenyl)-1,2,4-triazol-3- ylthio)acetate (Tiometrizol). It is known that this compound is quite active in the biological aspect of the substance. In the course of our work we studied the pharmacodynamics of morpholinum 2-(5-(pyridin-4-yl)- 4-(2-methoxyphenyl)-1,2,4-triazol-3-ylthio)acetate on rabbits. The analysis of the absorption spectra of serum samples, which have been obtained after administration of solution morpholinium 2-(5-(pyridin-4-yl)-4-(2- methoxyphenyl)-1,2,4-triazol-3-ylthio)acetate has been conducted and characteristic absorption band of the substance at 275 nm after 15 minutes has been registered. It is established by spectrophotometric studying of blood and urine of animals that potential medicine Tiometrizol generates the maximum concentration in blood after intravenous injection and after 24 hours it is not detected in blood also after 32 hours it is not detected in urine of animals. That is why this non-toxic medicine can be recommended for further testing.
Изучение фармакокинетики морфолиний 2-(5-(4-пиридил)-4-(2-метоксифенил)- 1,2,4-триазол-3-илтио)ацетата
The study of pharmacokinetics of morpholinium 2-(5-(4-pyridyl)-4-(2- methoxyphenyl)-1,2,4-triazol-3-ylthio)acetate
Keywords: 1,2,4-триазоли; фармакокінетика; морфоліній; 1,2,4-триазол; морфолиний; фармакокинетика; 1,2,4-triazol; morpholinium; pharmacokinetics